Reykjavík’s roadsides : using roadside vegetation as a source to increase biological diversity in urban environments - Hafliðadóttir, Hrönn (SLU/Dept. of Urban and Rural Development, 2018)
With the expansion and densification of urban environments, natural and man-made, open and green areas get lost for buildings and transportation systems. It is therefore crucial to take care of the green areas and ecologically favourable environments to support urban biodiversity. Proper plant selection, species composition, sustainable stormwater management and respect for ecosystem services and the planning site itself, are essential links to promote sustainable and biologically diverse urban environments, which at the same time preserve the city’s aesthetical values.